The Influence of the Problem Based Learning Model on the Learning Outcomes of Class XI Students at SMA Al-Washliyah 3 Medan - Putri Annisaa Silalahi; Muhammad Faisal Husna (International Journal of Educational Research Excellence (IJERE), 2023)
This research aims to see the influence of the Problem Based Learning learning model on student learning outcomes in class XI SMA Al-Washliyah 3 Medan. The background to this research is that student learning outcomes are still below average because students are less active in class and teachers still use conventional models which makes it difficult for students to understand Civics lessons in class. This type of research is classroom action research carried out in two cycles. The research instruments were observation sheets and tests. Data was obtained by means of quantitative analysis to calculate the percentage of completeness. Based on data analysis, it turns out that students' PPKn learning has increased with each cycle. The average test result score from cycle I to cycle II increased, in cycle I the average test result was 65.59 and in cycle II the average test result was 77.35. The increase in PPKn learning outcomes in cycle I was 23.53%, then increased in cycle II to 73.53%. The conclusion of this research is that applying the Problem Based Learning learning model can have a positive effect on improving student learning outcomes in class XI PPKn subjects at SMA Al-Washliyah 3 Medan.